Memproyeksikan Identitas Gender: Penggambaran Perempuan dalam Film Sutradara Perempuan - Ayu Kartika Julianingsih Tas'an; Rosnani Rosnani (Vox Populi, 2023)
This paper aims to assess the role of female filmmakers in the contemporary Indonesian film industries. Throughout history, the presence of women in the Indonesian film industry brings many effects on the way a woman is depicted on screen. As the portrayal of women in Indonesian films tends to be homogenous, many female filmmakers strive to give another image of women on screen and work against the stereotype of women in earlier Indonesian movies. Hence, this study argues that Indonesian female filmmakers challenge the depiction of women in the contemporary Indonesian film industry. This research uses a qualitative methodology, mainly textual analysis to have a deep understanding of way the Indonesian female filmmakers contribute to the depiction of women in film. By selecting two recent films produced by women, the research portrays women through its cinematic elements. The finding in this research demonstrates that Indonesian women filmmakers contribute to a different portrayal of women on screen and adds more discussion about how female filmmakers speak about the issue of women through their productions. Furthermore, the character of women in the selected film has a strong correlation with the local culture which is embedded in the social life of Indonesian. Hence, it can be concluded that Indonesian female directors contribute not only to the depiction of women but also to the discourse of women in Indonesian films